A Computer-Based Sustained Visual Attention Test for Pre-School Children: Design, Development and Psychometric Properties - Roohollah Zahedian Nasb; Malahat Akbarfahimi; Mohammad Reza Keyhani (Shiraz University of Medical Sciences, 2016)
Background: Sustained visual attention is a prerequisite for learning and memory. The early evaluation of attention in childhood is essential for their school and career success in the future. The aim of this study was to design, development and investigation of psychometric properties (content, face and convergent validity and test-retest and internal consistency reliability) of the computer - based sustained visual attention test (SuVAT) for healthy preschool children aged 4-6 with their special needs. Methods: This study was carried out in two stages: in the first stage computerbased SuVAT in two versions original and parallel were developed. Then the test-retest and internal consistency reliability using intra-class correlation and Cronbach's alpha coefficients respectively were examined; Face validity was calculated through ideas gathering from 10 preschool children and content validity evaluated using CVI and CVR method and convergent validity of SuVAT with CPT was assessed using Pearson correlation. Results: The developed test showed a good content and faces validity, and also had excellent test-retest reliability. In addition, the assessment of internal consistency indicated the high internal consistency of the test (Cronbach's alpha=0.869). SuVAT and CPT test demonstrated a positive correlation upon the convergent validity testing. Conclusion: SuVAT with good reliability and validity could be used as an acceptable sustained attention assessment in preschool children.